Effect of Stock Split and Dividend Announcement on Trading Volume in Companies Listed on the Indonesia Stock Exchange: Pengaruh Stock split Dan Pengumuman Deviden Terhadap Volume Perdagangan Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Chandrasisilia Celvina Kusuma; Wiwit Hariyanto (Academia Open, 2021)
This study aims to determine whether stock spills and dividend announcements affect the trading volume of companies listed on the Indonesia Stock Exchange for the 2017-2019 period with a total of 14 companies. This study uses a quantitative approach. By using secondary data where data collection is at the IDX, Faculty of Economics and Business, Muhammadiyah University of Sidoarjo or from the IDX official website. Data collection is done by tracing financial statements, annual reports and audit reports, trading volume reports and previous journals. The results of this study state that partially the Stock split variable has no significant effect on Trading Volume, while the Dividend Announcement variable has a significant effect on Trading Volume.